Childhood brain morphometry in children with persistent stunting and catch-up growth - Beena Koshy; Vedha Viyas Thilagarajan; Samuel Berkins; Arpan Banerjee; Manikandan Srinivasan; Roshan S. Livingstone; Venkata Raghava Mohan; Rebecca Scharf; Anitha Jasper; Gagandeep Kang (PLoS ONE, 2025)
Background Early childhood stunting affects around 150 million young children worldwide and leads to suboptimal human potential in later life. However, there is limited data on the effects of early childhood stunting and catch-up growth on brain morphometry. Methods We evaluated childhood brain volumes at nine years of age in a community-based birth-cohort follow-up study in Vellore, south India among four groups based on anthropometric assessments at two, five, and nine years namely ‘Never Stunted’ (NS), ‘Stunted at two years and caught up by five years’ (S2N5), ‘Stunted at two and five years and caught up by nine years’ (S2N9), and ‘Always Stunted’ (AS). T1-weighted magnetic resonance imaging (MRI) images were acquired using a 3T MRI scanner, and brain volumes were quantified using FreeSurfer software. Analysis of Variance (ANOVA) was used to determine the differences in brain volumetry between the stunting groups, with age and sex as covariates. The effect size ANOVA models was evaluated using Eta squared. Findings Amongst 251 children from the initial cohort, 178 children with a mean age of 9.54 underwent neuroimaging and considered for further analysis. The total brain volume, subcortical volume, bilateral cerebellar white matter, and posterior corpus callosum showed a declining trend from NS to AS. Regional cortical brain analysis showed significant lower bilateral lateral occipital volumes, right pallidum, bilateral caudate, and right thalamus volumes between NS and AS. Interpretation To the best of our knowledge, this first neuroimaging analysis to investigate the effects of persistent childhood stunting and catch-up growth on brain volumetry indicates impairment at different brain levels involving total brain and subcortical volumes, networking/connecting centres (thalamus, basal ganglia, callosum, cerebellum) and visual processing area of lateral occipital cortex.